Hydrological processes (water use and balance) in a coffee (Coffea arabica L.) monoculture and a coffee plantation shaded by Inga densiflora in Costa Rica - Siles Gutiérrez, Pablo (2007)
Tesis (Ph. D. ) -- CATIE. Escuela de Posgrado, Turrialba (Costa Rica), Université Henri Poincaré, 2007